Analisis Pelaksanaan Perhitungan dan Pembagian SHU Pada KPRI SMADA Palangka Raya - Noor Anisa; Dehen Erang; Windy Utami Putri (Edunomics Journal, 2023)
Analysis of the Implementation of Calculation and Distribution of SHU at KPRI SMADA at SMA Negeri 2 Palangka Raya. The location of this research is KPRI SMADA SMA Negeri 2 Palangka Raya which is located at Jalan K.S. Tubun No.02 Pahandut, Palangka Raya City. This cooperative was formed on January 25, 1988 with a cooperative legal entity No: 1057/BH/XIX/1989. This thesis was written with the aim of knowing the implementation of the calculation and distribution of SHU in the KPRI SMADA Cooperative in 2021; and to find out the distribution of SHU KPRI SMADA in 2021 in accordance with the provisions in the AD/ART KPRI SMADA SMA Negeri 2 Palangka Raya. This study uses a descriptive qualitative approach, this type of research uses a document studies, data collection methods used are documentation, interviews, and observation, and the data obatined is analyzed using the profit an loss formula. Based on the results of the study, it is known that the calculation and distribution of the remaining operating results (SHU) of KPRI "SMADA" at SMA Negeri 2 Palangka Raya in 2021, namely; (1) a) Total revenue minus total expenditure so as to produce Remaining Operating Results (SHU) of Rp. 721,639,036.93 of the calculation of the Remaining Operating Income (SHU) is in accordance with the Articles of Association and Bylaws (AD/ART) in the KPRI SMADA SMA Negeri 2 Palangka Raya report. b) The distribution of the remainder is determined based on; 25% reserve fund, 35% loan service, 20% deposit service, 7.5% management fund, 5% employee fund, 2.5% education fund, 2.5% social fund and 2.5% work area development fund. (2) Calculation and distribution of Operating Profits (SHU) in accordance with applicable regulations and provisions in AD/ART based on accounting principles, cooperatives, in accordance with the provisions of Law no. 25 of 1992 concerning cooperatives and AD/ART. (3) Calculation and Distribution of SHU for Members, namely; The distribution of SHU of maya members is Rp. 1,749,922; SHU dino of Rp. 877,608; bima SHU is 1,334,570, the higher the loan the higher the interest and Remaining Operating Income (SHU) obtained and the calculation and distribution is in accordance with accounting principles, cooperatives and the provisions of Law no. 25 of 1992 concerning cooperatives and in accordance with the Articles of Association (AD) and Bylaws (ART).